Facile preparation of single-atom Ru catalysts via a two-dimensional interface directed synthesis technique for the NRR. Issue 36 (14th April 2023) - Chen, Yao; Xu, Rui; Li, Yuchao; Cai, Lu; Yang, Yubo; Zheng, Yanxia; Zuo, Cuncun; Huang, Haofei; Wen, Zijian; Wang, Qian
Abstract : The rGO/NC interface, as a protective barrier, can effectively prevent the aggregation of Ru atoms during the repreparation process and promote the NRR process. Abstract : Through the catalysis system design of in situ Ru SACs (single atoms) anchored on a rGO/NC two-dimensional interface, we successfully realized the SA-Ru@rGO/NC electrocatalyst with high metal loading density at a relatively low temperature. The largest NH3 yield of 110.1 μg h −1 mgcat −1 and FE of 17.9% were achieved at −0.3 V under ambient conditions. The electronic environment of the catalyst was regulated by the electronic metal–support interaction, and the use of SACs had the advantages of inhibiting the hydrogen evolution reaction (HER) and enhancing N2 adsorption, which effectively improved the performance of electrocatalytic nitrogen fixation.